Mental Health in Primary Care: weaving family approach tools - Érika Vanessa Serejo Costa; Marta Celia Cunha; Marta Evelin de Carvalho; Jardel Alcântara Negreiros; Eliany Nazaré Oliveira; Francisco Rosemiro Guimarães Ximenes Neto (Universidad de Alicante, 2018)
The objective of this case study is to conduct analysis of the relations of individuals with mental disorders, with the use of family approach tools in the municipality of Tianguá - Ceará, Brazil, from April to June 2015. The information was collected through interviews and field diary, during home visits; followed by mapping and analysis of family assessment tools: typology, genogram, ecomap and impaired (mother and provider of the family) and three children had mental disorders: Carnation (Schizophrenia), Sunflower (severe mental disorder) and Margaret (mentally handicapped). This family lives in extreme social vulnerability according to the Coelho-Savassi Family Risk Scale (ERF-CS). The results showed a female single parent arrangement, scoring 32 at ERF-CS with frail social interaction and distant family relations, marked by mental decompensation and lack of specialized multidisciplinary support. The study shows the importance of using family approach tools to enhance practices and strengthen the role of the FHS/PHC. However, in view of complex cases alone, the FHS/PHC cannot be effective, requiring, therefore, matrix support of specialized network which provides more autonomy to the subjects.